8. THE IMPACT OF PERSONAL KNOWLEDGE MANAGEMENT ON EMPLOYEES’ PERFORMANCE AMONG PUBLIC SERVICE ORGANIZATION - Muhammad, Norrini; Mansor, Farah Ahlami; Hashim, Mimi Zazira; Omar, Siti Nur Zahirah (Journal of Islamic, Social, Economics and Development, 2024)
This study explores the impact of personal knowledge management (PKM) practices—specifically, the processes of retrieving, evaluating, organizing, collaborating, analyzing, presenting, and securing information—on employee performance in public service organizations. Employing a quantitative research methodology, data were collected through structured questionnaires, resulting in 108 valid responses for analysis using IBM SPSS Version 22.0. The findings reveal that PKM practices significantly impact employee performance. Notably, among the analyzed PKM practices, the processes of evaluating, organizing, analyzing and presenting information demonstrate a statistically significant impact on employee performance. In contrast, the other dimensions of PKM—retrieving, collaborating, and securing information—exhibit no substantial impact on performance outcomes. This study contributes valuable insights into the essential role of PKM within the public service sector and outlines significant implications for future research in this field.